Knowledge, Attitudes, and Practices Regarding Infection Prevention and Control Among Dental Students in Saudi Arabia: A Cross-Sectional Study - Daghriri, Alhussain; Almuraikhi, Turki; Alhawiti, Waleed; Alshammari, Falah; Alamri, Hamdan (Journal of Neonatal Surgery, 2025)
Background: Infection prevention and control (IPC) is vital in dental settings due to high risk of exposure to bloodborne pathogens and other infectious agents. Dental health care professionals (DHCPs), particularly trained students, must possess adequate knowledge, attitudes, and practices (KAPs) to ensure safe and effective clinical care. Methods: A cross-sectional questionnaire-based study was conducted among dental students in Saudi Arabia. The validated questionnaire assessed five domains: demographic data and PPE usage; knowledge and attitudes toward chronic viral infections (HBV, HCV, and HIV); occupational exposure and postexposure prophylaxis (PEP); vaccination and screening for bloodborne viruses and clinical readiness. Descriptive statistics, Z-score tests, and Kendall’s Tau-b correlation were used for analysis, with significance set at p < 0.05. Results: A total of 101 students, predominantly females (88.1%), participated. Interns constituted the largest group (43.6%). Most participants (81.2%) were actively involved in clinical care. High to very high perceived occupational risk was reported for HBV (64.3%), HCV (64.4%), and HIV (61.4%). While more than half of the students expressed a willingness to perform all dental procedures on infected patients (HBV: 56.4%, HCV: 53.5%, HIV: 50.5%), a considerable proportion preferred limiting procedures to those involving minimal hemorrhage. Enhanced infection control measures were strongly supported, although misconceptions persisted—particularly the belief among 37.6% of students that HCV is vaccine preventable. Students with less clinical exposure demonstrated greater anxiety and reluctance in treating infected patients. Conclusion: Dental students generally demonstrated positive attitudes toward awareness of infection control, but notable gaps remain in risk perceptions and knowledge about vaccine-preventable diseases. Curriculum enhancements focused on IPC training, ethical considerations, and hands-on clinical preparedness are recommended to address these deficiencies.